Asuransi Sosial Syariah bagi Muslim Indonesia - Fatkhul Muin; Rully Syahrul Mucharom (AHKAM : Jurnal Ilmu Syariah, 2015)
The basic concept of the insurance is because people need protection against any incident that occurs in the community such as illness and natural disasters. The article 14 In Law No. 2 of 1992 on  Insurance, that social insurance is a type of insurance to the implemented by the government for public welfare.  The current population is Moslem Indonesia reached 80%, therefore, the Indonesian Muslim community needs the systema syariah  social insurance.   The system of syariah social insurance where there are 2 (two) products, where there are participants and savings accounts tabarru’ and as managers by the BUMN (state corporation) in law No. 2 of 1992 on Insurance.DOI: 10.15408/ajis.v15i1.2854